Karakteristik Klinis Kasus Pterygium di Rumah Sakit Dr. Kariadi - dedi purnomo; Dina Novita; Winarto Winarto (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2020)
Introduction and Objective: Pterygium is a fibrovascular tissue growth of conjunctiva. The aim of this study was to report the clinical characteristic of pterygium cases in dr. Kariadi Hospital Semarang. Method: This is a retrospective study of pterygium patients medical records who went to surgery in Ophthalmology Department of Kariadi Hospital Semarang, from March 2012 to April 2017. The data of patient age, gender, occupation, laterality, site of pterygium, visual acuity, type of surgery, recurrences, and complications were collected. Descriptive statistics analysis was used to analyzed demographic and clinical profile of patient. Result: Seventy-six patients were included in this study consist of 61.8% were female and 31.2% were male. The mean age was 46.04 ± 12.76 years (range 18-65 years). Most of the patients were housewife (30.3%) and private worker (25%). Fifty-six percent of patients have unilateral pterygium and mostly on nasal site (90.79%). Twenty-five percent of patients underwent excision with limbal-autograft. Five patients (13.9%) have recurrences, therefore overall recurences rate was 13.9%, in which three patients (17.6%) without graft recurrence occured at first year treatment and two patients (9.5%) with graft recurrence occured at third year treatment. Most patients have best corrected visual acuity between 6/6 to 6/18 before and after treatment (40.7% and 55.26% respectively). Complications were recurrence (6.58%), post-operative refractive disorders (5.26%). Conclusion: pterygium patients mostly were housewife with unilateral and located on nasal site. Recurence rate of pterygium excision with conjungtivo limbal-autograft was smaller than bare sclera technique in which occured at 3 year of post operation.